Lymphoid Progenitor Cells from Childhood Acute Lymphoblastic Leukemia Are Functionally Deficient and Express High Levels of the Transcriptional Repressor Gfi-1 - Jessica Purizaca; Adriana Contreras-Quiroz; Elisa Dorantes-Acosta; Eduardo Vadillo; Lourdes Arriaga-Pizano; Silvestre Fuentes-Figueroa; Horacio Villagomez-Barragán; Patricia Flores-Guzmán; Antonio Alvarado-Moreno; Hector Mayani; Isaura Meza; Rosaura Hernandez; et al. (Clinical and Developmental Immunology)
Acute lymphoblastic leukemia (ALL) is the most frequent malignancy of childhood. Substantial progress on understanding the cell hierarchy within ALL bone marrow (BM) has been recorded in the last few years, suggesting that both primitive cell fractions and committed lymphoid blasts with immature stem cell-like properties contain leukemia-initiating cells. Nevertheless, the biology of the early progenitors that initiate the lymphoid program remains elusive. The aim of the present study was to investigate the ability of lymphoid progenitors from B-cell precursor ALL BM to proliferate and undergo multilineage differentiation. By phenotype analyses, in vitro proliferation assays, and controlled culture systems, the lymphoid differentiation potentials were evaluated in BM primitive populations from B-cell precursor ALL pediatric patients. When compared to their normal counterparts, functional stem and progenitor cell contents were substantially reduced in ALL BM. Moreover, neither B nor NK or dendritic lymphoid-cell populations developed recurrently from highly purified ALL-lymphoid progenitors, and their proliferation and cell cycle status revealed limited proliferative capacity. Interestingly, a number of quiescence-associated transcription factors were elevated, including the transcriptional repressor Gfi-1, which was highly expressed in primitive CD34+ cells. Together, our findings reveal major functional defects in the primitive hematopoietic component of ALL BM. A possible contribution of high levels of Gfi-1 expression in the regulation of the stem/progenitor cell biology is suggested.